Modern aspects of therapy of primary and secondary dystrophies of the cornea - Vakhova, Е.S.; Yani, Е.V.; Seliverstova, К.Е. (Rossiĭskiĭ oftalʹmologicheskiĭ zhurnal, 2018)
Dystrophy of the cornea is a pathological condition characterized by various manifestations of chronic corneal nutrition disorders. Surgical treatment of corneal dystrophy remains insufficiently available in many regions of Russia. Conservative therapy of corneal dystrophy can prevent the progression of the dystrophic process, retard the opacity of the cornea and maintain the visual acuity and the patient's ability to work for a sufficiently long time. Repeated courses of complex conservative therapy in primary corneal dystrophy allow: delaying the progression of the disease and stabilizing the dystrophic process in 23 to 65 % of cases, increasing visual acuity (averagely by 0.2-0.3) or maintaining the available vision in 35-72 % of patients, preventing the relapse of corneal erosions or ulcers, improving the quality of life and self-appraisal of patients with corneal dystrophy, maintaining their ability to work and professional fitness for a long time (up to 15-30 years). For citation: Vakhova Е.S., Yani Е.V., Seliverstova К.Е. Modern aspects of therapy of primary and secondary dystrophies of the cornea. Russian ophthalmological journal. 2018; 11 (1): 59-65. doi: 10.21516/2072-0076-2018-11-1-59-65 (In Russian).